A Thematic Review of Digital Technology Suitability in Improving Inter-OrganisationalCollaboration Workflows in the Malaysian Public Sector E-Payment Systems - Khairil Faizal Khairi; Naharudin Saadan; Soliha Sanusi (UIS Press, 2026)
Indexed by MyCite